'Dear Hélène'. Social use of college series - Pasquier, Dominique (Réseaux. The French journal of communication, 1996)
Summary: The television sitcom 'Hélène et les garçons' engendered a social phenomenon in France in the early nineties. Drawing on a questionnaire, interviews, observations and an analysis of fan mail, the author shows how the programme (a soap opera about college life) served as a medium for the definition of gender identity among pre-adolescents and adolescents. Reception of the series is characterized by a dual logic of intimate appropriation - based on emotional links with the characters - and collective negotiation of identities - based on interaction within peer groups and the family.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzQwNi9yZXNvLjE5OTYuMzMwNw